Development of mobile health-based interventions to promote physical activity in patients with head and neck cancer: a qualitative study - Ning, Yan; Dong, Zhen; Jia, Zehuan; Zhao, Wenting; Ding, Yongxia; Wang, Qian; Zhu, Ruifang; Han, Shifan (Frontiers in Public Health, 2023)
Background Despite the well-grounded benefits of physical activity (PA), poor compliance with the PA guidelines has been reported among head and neck cancer (HNC) patients. Mobile health (mHealth)-based interventions can help cancer survivors increase their PA levels and increase the reach or efficiency of rehabilitation services. However, there is limited knowledge about the needs and perceptions of HNC patients regarding these interventions. This study explored the perceptions and needs of HNC patients regarding mHealth-based PA programs before developing such interventions to ensure their improved effectiveness. Study design A constructivist qualitative study. Methods We purposively selected 17 adult HNC patients aged 40–80 years to determine their needs and perceptions of future mHealth-based PA programs. Semi-structured face-to-face interviews were conducted, and the data were analyzed via thematic analysis. The report followed the Consolidated Criteria for Qualitative Research Reports guidelines. Results Four themes were analyzed from the interview transcripts regarding the needs and perceptions of mHealth-based PA programs: (1) functionality needs; (2) system usage requirements; (3) social support; and (4) perceived barriers and facilitators. HNC patients expect highly customized and specialized mHealth interventions that consider individual factors, address their concerns about security, network, and cost, and prefer improved comfort. Moreover, they expect to receive support from their healthcare providers, families, and peers. Conclusion The study provides pragmatic ready-to-use recommendations to design interventions for inactive HNC patients to achieve the recommended PA levels. Future mHealth interventions should be tailored according to the needs of the HNC patients by utilizing perceived facilitators and removing perceived barriers to help them engage in PA actively.